Challenging Our Assumptions About Male and Female Preferences for Competition. Issue 4 (April 2017) - Robinson, Jill L.; Lipman‐Blumen, Jean
Abstract : The current article challenges the cultural stereotypes surrounding the behaviors men and women use to accomplish their goals, with a specific emphasis on competitive behavior. Using the Connective Leadership Model, we offer an in‐depth look at both how men and women differ in competitive leadership behaviors both across generations and time. The paper analyzed data gathered from the 1980‐2015, utilizing the L‐BL Achieving Styles Inventory (ASI). Examining over 10, 000 responses from U.S. upper‐ and middle‐level managers and first‐line supervisors, across industries, the results provide valuable insights into recent gender patterns. Our findings suggest that men appear to be responding to the social expansion of their behavioral choices by placing competitive behavior increasingly lower than other options and lower than they have in the past. Yet, men still engage in more competitive behavior than women. Curiously, Millennials of both sexes reported a counter‐intuitive uptick in competitive behavior. The current study offers important insights not only for leadership scholars, but for present and future leaders seeking to understand the influence of gender on the changing face of competitive leadership behavior.